Applying metaheuristic strategies in construction projects management - Wojciech Boejko (Journal of Civil Engineering and Management, 2012)
This work deals with the application of artificial intelligence instruments in a building schedule. In this article there was presented an original optimization scatter search algorithm taking into consideration both technological and organizational restrictions. This algorithm was applied to the real analysis of the industrial building project realization.